Answer:
The answer is the second option
![(x-1)^(2)+(y-4)^(2)= 4](https://img.qammunity.org/2020/formulas/mathematics/middle-school/2ofh81jrh30983z91713ow29uvodoaa08i.png)
Explanation:
The general equation of a circle is:
![(x-h)^(2)+(y-k)^(2)= r^(2)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/u0si3lgibqg2fgmpla4vl44b843hj4r6qo.png)
in this equation (h,k) is the center of the circle and r is the radius, so if the center is in (1,4) and the radius is 2, the values of the constants are:
h = 1
k = 4
r = 2
And the formula for this circle is:
![(x-1)^(2)+(y-4)^(2)= 2^(2)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/866jdstdt4bi0zs1hzwafw0ko401oohzi2.png)
![(x-1)^(2)+(y-4)^(2)= 4](https://img.qammunity.org/2020/formulas/mathematics/middle-school/2ofh81jrh30983z91713ow29uvodoaa08i.png)